An introvert female in Indonesian literature: Jungian psychology perspectives - Ahmadi, Anas; Artanti, Yeni; Baltazar, Cirilo; Colo, Heribertus Amaunut; Guterres, Antonio; Sarmento, Joao da Silva (Diksi, 2024)
The research aims to explore an introverted female depicted in Indonesian literature. Data sources used were a novel entitled Amba by Laksmi Pamuntjak.  The research was focused on the introversion of a female character named Amba. The data collection technique used was a literature review. Data analysis technique referred to literary psychology that consisted of identification, classification, reduction, synthesis, interpretation, and verification of data which were related to the mind and behaviors of the introvert female character. The results showed that Amba was an introverted female proven from the characteristics of (1) introversion female and shy behavior, (2) introversion female and indifferent behavior, (3) introversion female and loyalty, (4) introversion female and jealousy, and (5) introversion female and inner world. The results showed that Indonesian females tended to be introverted because they are Eastern females.